Hybrid project management solutions with multi-geographical teams - Bragança, C.; Lima, R. M.; Pereira, L.; Mateus, T. (International Journal of Learning and Change, 2023)
Delivering a project has several challenges to be addressed, and to mitigate them, multiple approaches have arisen and suggested as best practices to stakeholders satisfaction. This research presents a proposal to manage communication inside a virtual project team, adapting concepts from traditional and agile approaches into a hybrid framework, created using the action research spiral approach to evaluate the performance. It was possible to implement three action-research cycles, considering the spiral approach, starting will a diagnosis of the team, followed by action planning and implementation in a two month cycle, finishing with evaluation of the results and collection of feedbacks and potentials improvements. This paper describes all the process, tools and communication structure implemented in a product development project team of an industrial company for a period of six months. The results show that the team became project oriented, increasing trust among members and the alignment of dependencies between areas.